OPTIMIZATION OF THE DYNAMIC BEHAVIOUR OF STRUCTURES WITH ELEMENTS MADE OF PIEZOMATERIALS AND WITH EXTERNAL ELECTRICAL CIRCUITS - Iurlova, N.A.; Sevodina, N.V.; Oshmarin, D.A.; Iurlov, M.A. (Perm Federal Research Centre Journal, 2016)
In the present paper consideration is given to a passive method of vibration damping. Optimization of dissipative properties of electromechanical systems with external electric circuits is accomplished through a selection of the circuit parameters so as to provide the most effective damping of structure vibrations at the specified frequency. A coupled electro viscoelastic problem is solved. A mathematical model of electroviscoelastic body with external electric circuits is developed based on the equations of electrodynamics of deformable piezoelectric media under quasi-static approximation. In the presence of quasi-harmonic processes the viscoelastic properties of materials are taken into account via complex dynamic moduli. It is suggested that the problem on natural vibrations of viscoelastic bodies with piezoelectric elements and external electric circuits can be used to select the most effective schemes of problem solution. The problem of natural vibrations of electroviscoelastic systems is solved by using the computational algorithm developed by the project authors. The proposed algorithm is based on the standard finite element procedures and sub-routines developed by the authors to implement the computation algorithm, for example, the algorithm written in FORTRAN language to solve the algebraic problem of complex eigenvalues by the Muller method using different scenarios for selection of initial approximations.